APPLICATION OF ELECTRONIC SCHOLARLY PUBLISHING IN DIGITAL AGE: PROSPECTS AND CHALLENGES IN NIGERIAN UNIVERSITIES - Ridwan, Sani Murtala (European Scientific Journal, ESJ, 2015)
The significant technological infrastructure which are now beginning to offer services to prestigious large and smaller publishers, including some of the more trade-minded university presses on online and electronic means. Scholarship Online has demonstrated to the university press community that a large aggregation of quality monograph content, optimized for online scholarly use, generates strong usage and holds sufficient appeal to librarians to support a profitable business. Therefore, this paper highlighted general introduction f electronic scholarly publishing, from digital books to digital publishing, potential benefit of electronic scholarly publishing, ebook/electronic publishing as the future of scholarly communications system, open access and electronic scholarly commutation in Nigeria, the role of library in electronic scholarly publishing, archiving and preserving of electronic scholarly publishing, important of electronic scholarly publishing, and some of the challenges of electronic scholarly publishing in Nigeria. Recommendations for functional adoption of electronic scholarly publishing in Nigeria have also been given